Descripción de los parámetros de funcionamiento del grupo electrógeno Mirrlees Blackstone de la Central Térmica Catamayo de la Empresa Eléctrica Regional del Sur. - Peña Muñoz, Alex Ramiro (2015)
This paper aims to explain the principle of operation, operating parameters and maintenance routines Mirrlees Blackstone groups of Thermal Power Catamayo EERSSA. The thermal facilities available to the Southern Regional Electricity Company is concentrated in the Central Thermal Catamayo. There are 10 internal combustion engines the same that have been designed to work with diesel fuel. This central point is considered as only generated during peak hours to improve the system voltage and in times of low water at hydroelectric power station generates Advertise whole time until the emergency lasts. We choose the generators Mirrlees Blackstone to be the highest performance, the effective power of 2500 kW Through this work students and professors from the National University of Loja Area Energy Industries and Non-Renewable Natural Resources will conduct technical visits or internships, knowing the proper way to operate a generator.